Mitochondrial dysfunction in age-related sarcopenia: mechanistic insights, diagnostic advances, and therapeutic prospects - Huang, Yingtao; Wang, Chenchen; Cui, Haijian; Sun, Guangjiang; Qi, Xiaonan; Yao, Xiaosheng (Frontiers in Cell and Developmental Biology, 2025)
Sarcopenia is a progressive age-related decline in skeletal muscle mass, strength, and function, representing a significant health burden in older adults. Diagnostic criteria have been established that integrate measures of muscle mass, strength, and physical performance [e.g., European Working Group on Sarcopenia in Older People 2010 (EWGSOP1) and 2019 (EWGSOP2) criteria]. Mechanistically, sarcopenia is driven by hormonal changes, chronic inflammation, cellular senescence, and, importantly, mitochondrial dysfunction. Age-related declines in sex hormones and activation of myostatin impair muscle regeneration and metabolism, while chronic low-grade inflammation disrupts protein synthesis and accelerates proteolysis via the ubiquitin–proteasome system (UPS) and autophagy–lysosome pathway (ALP). The accumulation of senescent cells and their secretory phenotype further exacerbates muscle degeneration and functional decline. Mitochondrial dysfunction plays a central role, characterized by impaired biogenesis, excessive reactive oxygen species (ROS) production, compromised autophagy/mitophagy, and accumulation of mitochondrial DNA (mtDNA) mutations. These defects collectively disrupt muscle energy homeostasis, promoting atrophy. The AMPK/SIRT1/PGC-1α and mTORC1 signaling pathways, along with PINK1/Parkin-mediated and receptor-dependent mitophagy, are essential for regulating mitochondrial biogenesis, protein synthesis, and mitochondrial quality control. Current and emerging therapeutic approaches include resistance and endurance exercise, nutritional and pharmacological agents targeting mitochondrial health, and hormonal modulation. Innovative treatments such as senolytics, exerkines, and gene therapies show promise but require further validation. Future advances in mechanistic understanding, diagnostics, and therapeutic strategies offer hope for mitigating sarcopenia and improving the quality of life in aging populations.